An approach for rapid generation of interactive spider maps for public transport networks - Santos, Sara; Galvão, Teresa; Sobral, Thiago (EAI Endorsed Transactions on Smart Cities, 2020)
A spider map is a type of schematic map that allows one to answer questions like "From where I am, where can I go?", as it provides only the essential information for a given geographical area (hub), from which lines emerge, whilst keeping the geographic context. They are often designed manually for a limited set of locations, thus reducing its widespread adoption. Moreover, spider maps should conform to several design constraints, which turns the automated generation into a complex problem. Optimisation techniques have been applied to this problem, although existing solutions are time costly and require heavy computational power. This paper presents an approach to automatically generate feasible spider maps within a short execution time based on an algorithm that adapts state-of-the-art methods, producing adequate quality maps to be manipulated ininteractive media, based on the areas selected by the user. We report the results of a case study for areas in thecity of Porto, Portugal.